Effect of Rootstocks on Blooming Capacity and Productivity of AppleCultivars - Racskó, József; Nyéki, József; Szabó, Zoltán; Soltész, Miklós; Farkas, Ervin (Acta Agraria Debreceniensis, 2004)
The experiment with three different rootstock cultivars was set up in a commercial apple orchard at Nagykutas, which is situated in the western part of Hungary. The aim of our two-year-study was to determine the effect three different growing rootstock cultivars (M9, MM106 and seedling) on the flowering and productivity of 33 apple cultivars. Our observations included the following measurements: the date of the beginning and the end of flowering, flower density, fruit density, fruit numbers per tree and tree productivity. According to our results, it was found that the different growing rootstocks have a great determining effect on the above measurements. Our results showed that the flowering period was similar for all cultivars on the three different rootstocks. However, the flowering and the fruit setting decreased in the order M9, MM106 and seedling rootstocks. In contrast, the fruit number per tree followed, in decreasing order, MM106, seedling and M9 rootstocks.